Stress-induced redistribution of corticotropin-releasing factor receptor subtypes in the dorsal raphe nucleus - Waselus, Maria (2009)
BACKGROUND: The stress-related neuropeptide corticotropin-releasing factor (CRF) is involved in determining behavioral strategies for responding to stressors, in part through its regulation of the dorsal raphe (DR)-serotonin (5-HT) system. CRF(1) and CRF(2) receptor subtypes have opposing effects on this system that are associated with active vs. passive coping strategies, respectively. METHODS: Immunoelectron microscopy and in vivo single unit recordings were utilized to assess CRF receptor distribution and neuronal responses, respectively, in the DR of stressed and unstressed rats RESULTS: Here we show that in unstressed rats CRF(1) and CRF(2) are differentially distributed within DR cells, with CRF(1) being prominent on the plasma membrane, and CRF(2) being cytoplasmic. Stress experience reverses this distribution, such that CRF(2) is recruited to the plasma membrane and CRF(1) tends to internalize. As a consequence of this stress-induced cellular redistribution of CRF receptors, neuronal responses to CRF change from inhibition to a CRF(2)-mediated excitation. CONCLUSIONS: Given evidence that CRF(1) and CRF(2) activation are associated with distinct behavioral responses to stress, the stress-triggered reversal in receptor localization provides a cellular mechanism for switching behavioral strategies for coping with stressors.